Distinguishing lupus anticoagulants from factor VIII inhibitors in haemophilic and non‐haemophilic patients. Issue 5 (13th July 2018) - Rampersad, A. G.; Boylan, B.; Miller, C. H.; Shapiro, A.
Abstract : Introduction: Accurate diagnosis of an inhibitor, a neutralizing antibody to infused factor VIII (FVIII), is essential for appropriate management of haemophilia A (HA). Low‐titre inhibitors may be difficult to diagnose due to high rates of false‐positive inhibitor results in that range. Transient low‐titre inhibitors and false‐positive inhibitors may be due to the presence of a lupus anticoagulant (LA) or other non‐specific antibodies. Fluorescence immunoassay (FLI) to detect antibodies to FVIII is a sensitive method to identify inhibitors in HA. Evaluations of antibody profiles by various groups have demonstrated that haemophilic inhibitors detected by Nijmegen‐Bethesda (NBA) and chromogenic Bethesda (CBA) assays correlate with positivity for anti‐FVIII immunoglobulin (Ig) G1 and G4. Aim: This study sought to determine whether FLI could distinguish false‐positive FVIII inhibitor results related to LAs from clinically relevant FVIII inhibitors in HA patients. Methods: Samples from haemophilic and non‐haemophilic subjects were tested for LA, specific FVIII inhibitors by NBA and CBA, and anti‐FVIII immunoglobulin profiles by FLI. Results: No samples from LA‐positive non‐haemophilic subjects were positive by FLI for anti‐FVIII IgG4. Conversely, 91% of NBA‐positive samples from haemophilia subjects were positive for anti‐FVIII IgG4. Two of 11 haemophilia subjects had samples negative for anti‐FVIII IgG4 and CBA, which likely represented LA rather than FVIII inhibitor presence. Conclusions: Assessment of anti‐FVIII profiles along with the CBA may be useful to distinguish a clinically relevant low‐titre FVIII inhibitor from a transient LA in HA patients.